Epigenetics: a new frontier in dentistry. (24th February 2014) - Williams, SD; Hughes, TE; Adler, CJ; Brook, AH; Townsend, GC
Abstract: In 2007, only four years after the completion of the Human Genome Project, the journal Science announced that epigenetics was the 'breakthrough of the year'. Time magazine placed it second in the top 10 discoveries of 2009. While our genetic code (i.e. our DNA) contains all of the information to produce the elements we require to function, our epigenetic code determines when and where genes in the genetic code are expressed. Without the epigenetic code, the genetic code is like an orchestra without a conductor. Although there is now a substantial amount of published research on epigenetics in medicine and biology, epigenetics in dental research is in its infancy. However, epigenetics promises to become increasingly relevant to dentistry because of the role it plays in gene expression during development and subsequently potentially influencing oral disease susceptibility. This paper provides a review of the field of epigenetics aimed specifically at oral health professionals. It defines epigenetics, addresses the underlying concepts and provides details about specific epigenetic molecular mechanisms. Further, we discuss some of the key areas where epigenetics is implicated, and review the literature on epigenetics research in dentistry, including its relevance to clinical disciplines. This review considers some implications of epigenetics for the future of dental practice, including a 'personalized medicine' approach to the management of common oral diseases.